Confronting my Palestinianess in Writing Pedagogies: A Critical View from Lebanon - Al-Sayyed, Amany (Critical Education, 2026)
This article offers an auto-theoretical, exploratory account of teaching writing as a Palestinian educator at the American University of Beirut in 2023–2024 during the war on Gaza and the escalation of violence in Lebanon. Written in a series of chronologically organized vignettes, the manuscript blends memoir, correspondence, lesson plans, and critical pedagogy to document how war enters the classroom through microaggressions, silencing, and institutional failure to recognize politically situated harm. Drawing inspiration from the essay tradition the article foregrounds process, uncertainty, and affect as legitimate forms of scholarly inquiry. Reflections on formative teachers in Canada, a Jewish-Canadian childhood friendship, and intergenerational memory illuminate how race, identity, and worldliness shape pedagogical becoming. The article situates experiential teaching during genocide within composition studies, arguing for the exploratory essay as an ethical and pedagogical response to crisis. It further details curricular revisions undertaken during wartime, including collaborative assessment, anti-thesis essay structures, and the use of fairytales—particularly Palestinian children’s literature—as a means of restoring imagination, solidarity, and care. Ultimately, the article testifies to the necessity of courageous dialogue, institutional accountability, and pedagogies that resist silence while affirming relational hope amid devastation.